EFFECTIVENESS OF COMBINING MECHANICAL SUCTION WITH PROSTAGLANDIN THERAPY IN MANAGING PYOMETRA IN A HOLSTEIN FRIESIAN CROSSBRED COW - R. Arun; S. Alagar; S. Rangasamy; A. Methai; G. Nishrath Banu; P.N. Richard Jagatheesan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A Holstein Friesian crossbred cow after six months of second calving was presented to the Veterinary Clinical Complex, Veterinary College and Research Institute, Theni, with a history of whitish vaginal discharge for the past two weeks. Rectal examination revealed bilaterally distended uterine horns with no palpable foetal structures and purulent material was expelled during the examination. Ultrasound examination revealed hyperechoic contents in both the uterine horns and a mature corpus luteum in the right ovary. Based on the clinical and ultrasound findings, the case was diagnosed as pyometra. Approximately 1.6 litters of purulent materials were evacuated using a suction apparatus and inj. PGF2αwas administered on the same day. The cow was treated with parenteral antibiotic, antihistamine and intrauterine antibiotic therapy for five days. After a month of sexual rest, a follow-up ultrasound examination revealed a normal uterus with no signs of pathology and the cow was subsequently inseminated. The case of open type pyometra in the lactating Holstein Friesian crossbred cow was successfully treated by evacuating the purulent material using a suction apparatus and followed by therapeutic management.